IMPLEMENTASI METODE SEMONSTRASI PADA MATA PELAJARAN PAI MATERI WUDHU DI SD NEGERI 3 GUNTUNG MANGGIS - Maysarah; Miftahul Jannah (Program Studi PGMI STAI Al Falah Banjarbaru, 2026)
This study discusses the implementation of the demonstration method in Islamic Religious Education (PAI) on ablution at Guntung Manggis 3 Elementary School. This study aims to determine the implementation of the demonstration method in Islamic Religious Education (PAI) on ablution at Guntung Manggis 3 Elementary School and its supporting and inhibiting factors. The subjects in this study were Islamic Religious Education (PAI) teachers, while the objects of this study were the implementation of the demonstration method in Islamic Religious Education (PAI) on ablution at Guntung Manggis 3 Elementary School and its supporting and inhibiting factors. This field research used a descriptive qualitative approach. The research object was non-participant observation, structured interviews, and documentation. Data processing was carried out using descriptive qualitative data collection, classification, editing, and interpretation techniques, followed by analysis. Conclusions were then drawn inductively. Based on the research results, it was found that the implementation of the demonstration method in the Islamic Religious Education (PAI) subject of ablution at SD Negeri 3 Guntung Manggis was carried out through several steps: the planning stage involved developing teaching modules, preparing materials, providing video-based learning media, and planning seating arrangements. The implementation stage involved delivering the material by writing key points on the board and demonstrating ablution in its entirety. The evaluation stage involved teacher reflection and evaluation using assessment instruments. Supporting factors included infrastructure, teachers as good instructors, and inhibiting factors included student conditions, teacher skills, and time constraints.